Design and Development of a Web-Based Mosque Financial Management Information System Using the Incremental Method - Amri, M Choirul; Anjani, Retno; Rasyid, Abdul; Pradana, Riski Ananta; Zufria, Ilka (Journal of Computer Science and Informatics Engineering, 2025)
Nur Hidayah Mosque in Dusun III, Tuntungan I Village, Pancur Batu District, Deli Serdang Regency, faces challenges in financial management, which is still conducted manually using cash books and printed reports. This manual system leads to delays, recording errors, and difficulties in monitoring and evaluating finances. To improve efficiency, accuracy, and transparency, this study designs and develops a web-based financial management information system using the incremental development method. The system allows mosque administrators, particularly the admin and treasurer, to digitally record income and expenses, generate automatic financial reports, and store data in a structured and easily accessible format. Features such as automatic recap and digital archiving further support transparency and accountability. The implementation of this system is expected to significantly enhance the performance of mosque financial management by providing faster and more organized data access while minimizing manual recording errors. This system contributes to the modernization of mosque financial administration and can serve as a reference for similar future research